21st Century Elementary School Management: CreativeStrategies towards Meaningful Learning - Gusliana, Evi; Wahyudi, Apri; Nurjanah, Siti; Umurohmi, Ulfah (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The transformation of elementary school management in the 21st century requires a creative strategic approach to create meaningful and relevant learning. This study aims to analyze creative management strategies in the context of elementary school education that can support meaningful learning. This type of research uses literature studies. Data collected through digital databases such as Google Scholar, Research Gate, Sinta, and official documents from the Ministry of Education and Culture published in the period 2020 to 2025. The literature used includes national and international journals, educational books, and educational policy documents. Data analysis was carried out thematically with a thematic content analysis approach, namely by identifying conceptual patterns from the contents of the literature related to educational management strategies. The results of the study show that there are four main strategies that support meaningful learning in the 21st century, namely: (1) transformational leadership that encourages changes in school culture and adaptive learning; (2) empowering teachers as agents of change who are able to design innovative and collaborative learning; (3) strengthening a positive school culture that supports student character and motivation; and (4) targeted technology integration to support personalized and interactive learning. These four strategies synergistically form an inclusive, adaptive, and sustainable educational ecosystem. So it can be concluded that 21st century elementary school management that adopts these four strategies is able to create a learning environment that supports the development of students' character and competence holistically.